1998
DOI: 10.1159/000012718
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Turnover, Lipoprotein Lipase Activity, and Fat Cell Size in Adipose Tissue of Rats during the First 2 Weeks of Pregnancy

Abstract: Understanding the biological function of the fat retained during pregnancy is important when estimating energy needs during reproduction. Women as well as rats are often considered to gain fat at specific anatomical sites during pregnancy and use this fat as a source of energy during lactation. However, mobilized body fat covers only a minor part of the energy needed by the lactating rat dam. In this paper, fat cell size, lipoprotein lipase activity, as well as triglyceride turnover in parametrial and subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Paraovarian adipocytes are also significantly larger in rats at 19 days of pregnancy than in virgin rats [20]. Sohlstrom et al demonstrated that pregnancy increases the size of rat parametrial, but not of subcutaneous adipocytes [14]. Our results are compatible with those published reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Paraovarian adipocytes are also significantly larger in rats at 19 days of pregnancy than in virgin rats [20]. Sohlstrom et al demonstrated that pregnancy increases the size of rat parametrial, but not of subcutaneous adipocytes [14]. Our results are compatible with those published reports.…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, adipose tissues were fixed in 10 % formaldehyde and stored at 4 8C. The size distribution was determined in osmium fixed fat cells and the diameters of 100 cells were measured microscopically as described by the same individual [14].…”
Section: Fat-cell Sizementioning
confidence: 99%